"They Overestimate Me All the Time:" Exploring Imposter Phenomenon among Indian Female Software Engineers. Issue 2 (December 2021) - Maji, Sucharita
Imposter phenomenon is defined as a self-perception of intellectual fraudulence despite achieving objective success and accomplishments. Imposter phenomenon has been rigorously explored among high-achieving career professionals. The present qualitative study is an attempt to explore imposter phenomenon experiences among female software engineers in the Indian Information and Technology sector. The data, derived through in-depth and semi-structured interviews, has been analysed through a hybrid of an inductive and a theoretical thematic analysis method. Clance and Imes' (1978, Psychother: Theory Res Pract, 15(3):241) article, "The Imposter Phenomenon in High Achieving Women: Dynamics and Therapeutic Intervention, " has been used for screening the sample and also, as a theoretical lens. The study reveals that external attribution of success, fear of failure, anxiety, and devaluing accomplishments are core psychological processes associated with the imposter phenomenon experience. The current work further found that parenting patterns characterized by lack of praises, comparison among siblings, lack of trust in children's potential, and strict gender values are significant antecedents of Imposter Phenomenon.